2018
DOI: 10.21037/jtd.2018.03.130
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic navigation bronchoscopy—Chungnam National University Hospital experience

Abstract: The ENB-guided dye localization by a well-trained thoracic surgeon enables accurate intraoperative identification of GGN or a small pulmonary nodule, with minimal complications and enables minimally invasive surgery including single port surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…In our cohort, there were no procedural complications and the dye marking was considered successful in 91% (21/23) of the cases. This is consistent with previous reports concerning ENB‐guided pleural dye marking . In comparison, localization with hookwire and CT‐guided dye marking typically has success rates of 80‐100% but with procedural related complications of 15%‐50%, higher than observed in the current ENB study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our cohort, there were no procedural complications and the dye marking was considered successful in 91% (21/23) of the cases. This is consistent with previous reports concerning ENB‐guided pleural dye marking . In comparison, localization with hookwire and CT‐guided dye marking typically has success rates of 80‐100% but with procedural related complications of 15%‐50%, higher than observed in the current ENB study.…”
Section: Discussionsupporting
confidence: 92%
“…Of the 232 biopsy subjects with Stages I‐II lung cancer in first interim analysis of NAVIGATE there were 87 who had a surgical procedure and of those, 65 (75%) had no prior ENB‐guided dye or fiducial marking. There have been 15 clinical studies (excluding single‐patient case reports) concerning ENB‐guided dye localization and only three have enrolled over 50 patients . These numbers suggest that perhaps dye marking is not underutilized, but rather not needed frequently.…”
Section: Discussionmentioning
confidence: 99%
“…15 Cho et al also used ENB-guided dye markings for 32 lesions in 25 patients to localize pulmonary nodules and achieved an 87.5% success rate. 24 Meanwhile, ENB-guided transbronchial approach has a relatively low incidence rate of procedure-related complications. 15,[24][25][26] Most studies have reported no specific complications except mild intrabronchial bleeding; one large scale study of 1000 subjects described the occurrence of pneumothorax, bronchopulmonary hemorrhage, and respiratory failure in 4.9, 2.3, and 0.6% cases, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…24 Meanwhile, ENB-guided transbronchial approach has a relatively low incidence rate of procedure-related complications. 15,[24][25][26] Most studies have reported no specific complications except mild intrabronchial bleeding; one large scale study of 1000 subjects described the occurrence of pneumothorax, bronchopulmonary hemorrhage, and respiratory failure in 4.9, 2.3, and 0.6% cases, respectively. 13 Nonetheless, most existing studies on ENB-guided methods were conducted only for one or two pulmonary nodules.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation